Exosome-Derived microRNA: Potential Target for Diagnosis and Treatment of Sepsis - Yujie Xiao; Yixuan Yuan; Dahai Hu; Hongtao Wang (Journal of Immunology Research)
Exosome-derived microRNAs (miRNAs) are emerging as pivotal players in the pathophysiology of sepsis, representing a new frontier in both the diagnosis and treatment of this complex condition. Sepsis, a severe systemic response to infection, involves intricate immune and nonimmune mechanisms, where exosome-mediated communication can significantly influence disease progression and outcomes. During the progress of sepsis, the miRNA profile of exosomes undergoes notable alterations, is reflecting, and may affect the progression of the disease. This review comprehensively explores the biology of exosome-derived miRNAs, which originate from both immune cells (such as macrophages and dendritic cells) and nonimmune cells (such as endothelial and epithelial cells) and play a dynamic role in modulating pathways that affect the course of sepsis, including those related to inflammation, immune response, cell survival, and apoptosis. Taking into account these dynamic changes, we further discuss the potential of exosome-derived miRNAs as biomarkers for the early detection and prognosis of sepsis and advantages over traditional biomarkers due to their stability and specificity. Furthermore, this review evaluates exosome-based therapeutic miRNA delivery systems in sepsis, which may pave the way for targeted modulation of the septic response and personalized treatment options.